IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF NUMBERED HEADS TOGETHER (NHT) TYPE ON THE SUBJECT OF STATISTICS AT VOCATIONAL HIGHT SCHOOL - Afifah, Ani; Fibriyani, Vita (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This study Purpose to describe the steps of cooperative learning model of numbered heads together (NHT) Type that can enhace students' understanding on the subject of statistics. Subject of study are all students of XI class Health vocational hight school of Al-Yasini. This type of research is a action research that refers to the O'Leary model. The data collected is derived from the work of the student worksheet, final of cycle test, observation result of teacher and student activities. The results of observation indicate that the activity of teacher and student have fulfilled good category, (2) percentage of students completion in solving problems in student worksheet more than 75%.